Topological Characteristics of Obstacles and Nonlinear Rheological Fluid Flow in Presence of Insulated Fins: A Fluid Force Reduction Study. (18th August 2021) - Majeed, Afraz Hussain; Jarad, Fahd; Mahmood, Rashid; Saddique, Imran
Abstract : In this work, a comprehensive study of fluid forces and thermal analysis of two-dimensional, laminar, and incompressible complex (power law, Bingham, and Herschel–Bulkley) fluid flow over a topological cross-sectional cylinder (square, hexagon, and circle) in channel have been computationally done by using finite element technique. The characteristics of nonlinear flow for varying ranges of power law index 0.4 ≤ n ≤ 1.6, Bingham number 0 ≤ Bn ≤ 50, Prandtl number 0.7 ≤ Pr ≤ 10, Reynolds number 10 ≤ Re ≤ 50, and Grashof number 1 ≤ Gr ≤ 10   have been examined. Considerable evaluation for thermal flow field in the form of dimensionless velocity profile, isotherms, drag and lift coefficients, and average Nusselt number Nu avg is done. Also, for a range of Bn, the drag forces reduction is observed for circular and hexagonal obstacles in comparison with the square cylinder. At Bn = 0   corresponding to Newtonian fluid, maximum reduction in drag force is reported.